Politiche di sviluppo place-based e distrettualità in agricoltura. Il caso lombardo - Bocchi, Stefano; Borasio, Mariella (Scienze del Territorio, 2014)
The Local Agro-food Systems (LAS), defined as systems alternative to the global food model, are based on the organization, management, optimization of the complex relationships among agricultural production, transformation, distribution and consumption in a Region, represent an efficient leverage for real innovative place based policies. The developing process occurring around the Milan metropolitan area, including many farmers, local authorities, citizens, local boards, is activating new innovation dynamics for the entire area.